The The Influence of Culture-Based Communication on Adolescent Decision-Making Regarding STDs and HIV/AIDS in Semarang, Central Java, Indonesia - Sujianto, Untung; Dwi Hastuti, Yuni; Kusuma, Henni; Ropyanto, Chandra; Hidayati, Wahyu (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
This study explores how communication rooted in local cultural values in Central Java influences adolescents' capacity to make appropriate decisions regarding the risks of sexually transmitted diseases and human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). Adolescents in Central Java are highly vulnerable to the risks of sexually transmitted diseases and HIV/AIDS given the sociocultural dynamics that influence their sexual behaviour. This phenomenon is exacerbated by the shift in the age of sexual initiation to an increasingly early age, from 18-19 years to 17-18 years, based on data from the Indonesian Demographic and Health Survey. The increase in the prevalence of risky sexual behaviour among adolescents requires a comprehensive approach, particularly through culture-based communication, to improve the ability to make appropriate decisions in the face of the threat of STDs and HIV/AIDS. Keywords: Communication, culture, STDs, HIV AIDS